Cruelty and Tragedy: Cathartic Journey in Peter Shaffer's Equus - Sena Baltaoglu (Ideas: Journal of English Literary Studies)
The concept of catharsis has evolved much since Aristotle defined it in Poetics as the purgation of feelings such as pity and fear caused by an imitation of a tragic action. As Antonin Artaud argued in Theatre and Its Double, the theatre of cruelty aims to arouse a therapeutic effect in order to discharge the negative feelings of the audience. Although Peter Shaffer's Equus (1973) is widely acknowledged as an example of epic theatre, it also evokes the characteristics of theatre of cruelty with its portrayal of overt violence and its affective/emotional reflections on the main characters. This includes both the purification of feelings and psychological clarification of these characters as represented in the play. The relationship between the psychiatrist Martin Dysart and his patient Alan Strang can be regarded as a mutual play within the play, which makes them each other's audience as well. Relying on Freudian and Artaudian frameworks, this paper aims to illustrate how the play reveals the modern facet of the concept of catharsis by claiming that both Dysart and Alan discharge their negative feelings in a therapeutic relationship.